Functional analysis of clinical BARD1 germline variants - Toh, Ming Ren (Cold Spring Harb Mol Case Stud, 2019)
Germline pathogenic variants in BRCA1/2 account for one-third of familial breast cancers. The majority of BRCA1 function requires heterodimerization with BARD1. In contrast to BRCA1, BARD1 is a low-penetrance gene with an unclear clinical relevance, partly because of limited functional evidence. Using patient-derived lymphoblastoid cells, we functionally characterized two pathogenic variants (c.1833dupT, c.2099delG) and three variants of uncertain significance (VUSs) (c.73G>C, c.1217G>A, c.1918C>A). Three of these patients had breast cancers, whereas the remaining had colorectal cancers (n = 3). Both patients with pathogenic variants (c.1833dupT, c.2099delG) developed breast cancers with aggressive disease phenotypes such as triple-negative breast cancer and high cancer grades. As BARD1 encompasses multiple functional domains, including those of apoptosis and homologous recombination repair, we hypothesized that the function being impaired would correspond with the domain where the variant was located. Variants c.1918C>A, c.1833dupT, c.1217G>A, and c.2099delG, located within and proximal to apoptotic domains of ankyrin and BRCT, were associated with impaired apoptosis. Conversely, apoptosis function was preserved in c.73G>C, which was distant from the ankyrin domain. All variants displayed normal BRCA1 heterodimerization and RAD51 colocalization, consistent with their location being distal to BRCA1—and RAD51-binding domains. In view of deficient apoptosis, VUSs (c.1217G>A and c.1918C>A) may be pathogenic or likely pathogenic variants. In summary, functional analysis of BARD1 VUSs requires a combination of assays and, more importantly, the use of appropriate functional assays with consideration to the variant's location.